Immunotherapy: insights from advanced disease - Tolaney, Sara M. (Henry Stewart Talks, 2019)
Checkpoint inhibitor therapy in breast cancer: focus on TNBC, Limited activity for checkpoint inhibitor monotherapy in metastatic TNBC, Atezolizumab + Nab-Paclitaxel: standard first line therapy for patients with metastatic PDL1 and, Combination treatment with checkpoint inhibitor therapy in HR+ and HER2+ breast cancer, Ongoing studies evaluating other strategies in breast cancer, The future: combination of checkpoint inhibitors and chemotherapy